2022
DOI: 10.1063/5.0070824
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-periodical kinetic instabilities in minimum-B confined plasma

Abstract: We present the results of an experimental investigation of quasi-periodical kinetic instabilities exhibited by magnetically confined electron cyclotron resonance heated plasmas. The instabilities were detected by measuring plasma microwave emission, electron losses, and wall bremsstrahlung. The instabilities were found to be grouped into fast sequences of periodic plasma losses, separated by ∼100 µs between the bursts, followed by 1–10 ms quiescent periods before the next event. Increasing the plasma energy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Some experimental campaigns probing the unstable plasma regime have been performed in the time-averaged mode using HPGe and cadmium-tellurium (CdTe) semiconductor detectors. 18,19,40 These studies have revealed that the shape of the temporally averaged bremsstrahlung spectrum does not significantly change between the stable and unstable plasma regimes. The result can be explained by the short duration (at the level of microseconds) of the instability burst and the properties of the detector system.…”
Section: Article Scitationorg/journal/rsimentioning
confidence: 99%
See 2 more Smart Citations
“…Some experimental campaigns probing the unstable plasma regime have been performed in the time-averaged mode using HPGe and cadmium-tellurium (CdTe) semiconductor detectors. 18,19,40 These studies have revealed that the shape of the temporally averaged bremsstrahlung spectrum does not significantly change between the stable and unstable plasma regimes. The result can be explained by the short duration (at the level of microseconds) of the instability burst and the properties of the detector system.…”
Section: Article Scitationorg/journal/rsimentioning
confidence: 99%
“…38, Izotov et al demonstrated the direct measurement of the energy distribution of axially escaping electrons from a stable ECR plasma using the ion source spectrometer magnet-originally designed for the m/q separation of multiply charged ions-as an electron energy analyzer. The technique has been used also in other studies for investigations of both stable and unstable ECR plasmas 39,40 in the time-averaged mode, i.e., by measuring the average electron current for each electron energy step. As plasma instabilities are characterized by the abrupt current transients, this time-averaged method provides only limited information of the expelled electrons.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation